Ligand Exchange Processes on Solvated Lithium Cations. II. Complexation by Cryptands in γ-Butyrolactone as Solvent - Pasgreta, Ewa; Puchta, Ralph; Galle, Michael; van Eikema Hommes, Nico; Zahl, Achim; van Eldik, Rudi (Journal of Inclusion Phenomena and Macrocyclic Chemistry, 2007)
Kinetic studies on Li exchange between the cryptands C222 and C221, and γ-butyrolactone as solvent were performed as a function of ligand-to-metal ratio, temperature and pressure using Li NMR. The thermal rate and activation parameters are: C222: k = (3.3 ± 0.8)×10 M s, ΔH = 35 ± 1 kJ mol and ΔS = -41 ± 3 J K mol; C221: k = 105 ± 32 M s, ΔH = 48 ± 1kJ mol and ΔS = -45 ± 2 J K mol. Temperature and pressure dependence measurements were performed in the presence of an excess of Li. The influence of pressure on the exchange rate is insignificant for both ligands, such that the value of activation volume is around zero within the experimental error limits. The activation parameters obtained in this study indicate that the exchange of Li between solvated and chelated Li ions follows an associative interchange mechanism. © Springer Science+Business Media B.V. 2007.
Keywords: gamma-butyrolactone; cryptands; exchange mechanism; Lithium